IMPLEMENTASI COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN PELABUHAN INTERNASIONAL DI SELAT SUNDA SEBAGAI ALTERNATIF JEMBATAN SELAT SUNDA: - Dedi Komarudin; Ika Sartika (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This research examines the application of collaborative governance in the context international port development as an alternative of the Sunda Strait Bridge project in the region. Using a qualitative approach and bibliometric analysis, this study explores the dynamics between stakeholders, barriers to implementing collaborative governance, and potential synergies that can be optimized. The results show that despite the high complexity and power imbalances among actors, collaborative governance has great potential to produce comprehensive and sustainable solutions. However, its implementation is still constrained by various factors, including changes in political policies and differences in priorities among stakeholders. This study identifies several key elements in the collaboration process, such as face-to-face dialogue, commitment to the process, and shared understanding of the project vision. The analysis also indicates that international port development may be a more feasible and sustainable alternative compared to JSS. Based on these findings, this research suggests several strategies to improve the effectiveness of collaborative governance, including the establishment of a more structured multi-stakeholder forum, development of a shared information system, and enhancement of collaborative capacity among actors. The conclusions and recommendations from this study can provide valuable input for the planning and implementation of other strategic infrastructure projects in Indonesia.